Differences in high school students' mathematical representation ability in homogeneous classes: Which is better? - Iqlides Ahmad Miyaqi; Insih Wilujeng; Dadan Rosana; Najilul Barokah (Momentum: Physics Education Journal, 2024)
Mathematical representation is one of the higher-order thinking skills needed by students in analyzing physics cases as a form of proving the truth of understanding. Referring to the inconsistencies in the results of research on mathematical representation involving gender and the phenomenon of the high ability of female students in heterogeneous classes, it is suspected that there is a relationship between class type and mathematical representation. This study aims to analyze the increase in students' mathematical representation abilities in terms of gender differences in homogeneous classes. The research subjects consisted of class X high school students in Bantul, Indonesia, consisting of 26 boys and 27 girls. The research instrument was 5 physics questions that referred to indicators of mathematical representation. Data analysis to find out how the category of mathematical representation increases using the N-Gain index. The results of this study were (1) the improvement in the ability of the male students' mathematical representation in the medium category was superior to that of the female students, (2) the improvement in the ability to make mathematical expressions and use visual representations was better for the male students, and (3) the ability of the female students in terms of making image representations better than male students. This research implies that further research is needed to be related to the causes of students' misinterpretation in dealing with physics test.